Do Budget Deficit Crowds out Private Investment: A Case of Tanzanian Economy - Mwigeka, Samwel (American Journal of Trade and Policy, 2015)
The existing high budget deficit in Tanzanian economy has created an immense concern among economic policy analysts. The study investigates whether budget deficits crowd out or crowd in private investment in Tanzania, using annual data covering the period from 1970 to 2012. Using the Johansen cointegration test suggests there is at least one cointegration vector among these variables. Under such circumstances, we employed a vector error correction model (VEC), since it offers more and better information compared to other data generation processes. The results point to a close long–term relationship between private investment, and other variables included in the study. Results suggest that budget deficits significantly crowds out private investment. These results substantiate the theoretical predictions and are also supported by previous studies. The paper recommends that government should redirect it fiscal policy that would favor the private investor by discouraging high government expenditure and maintaining a low fiscal deficit. Also, to avoid crowding out effect, capital market should be used to finance budget deficit. JEL Classifications Code: H6